Peningkatan Menulis Teks Prosedur Dengan Menggunakan Media Youtube Pada Siswa Kelas X I SMA Negeri I Kisaran Tahun Ajaran 2024/2025 - Rahayu, Sri; Lubis, Juwita; Sinaga, Monica Jeliana; Panjaitan, Ruth Meilati; Simanjuntak, Torop YA (STKIP ROKANIA, 2024)
The purpose of this study was to describe how the flipped classroom approach helped class XI students at SMA NEGERI 1 KISARAN enhance their procedural text writing skills for the 2023–2024 academic year. Classroom Action Research using a PTK Kemmis and McTaggart design is this kind of study. The four steps of the research process are planning, implementation, observation, and reflection. The process is organized like a cycle. Methods for gathering data that include testing, observation, and documenting. 23 SMA Negeri 1 Kisaran class XI students for the 2024/2025 school year served as the research subjects.The study's findings demonstrated that, of the 23 students who had finished their studies, 19 had obtained 80% learning completion in the pre-action tasks, while the other 4 had not yet finished their studies. Cycle 1: 9 students, or 39%, did not finish it, compared to 14 students, or 61%, who did. In cycle 2, eighty-nine pupils, or 83%, were complete. Four pupils, or 17 percent, had not finished. Based on this, it can be said that students in class XI at SMA Negeri 1 Kisaran can enhance their procedural text writing skills by implementing the flipped classroom approach in the 2024/2025 academic year